1992
DOI: 10.1148/radiology.184.1.1609108
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer: serial MR imaging before and after primary radiation therapy--a 2-year follow-up study.

Abstract: Serial magnetic resonance imaging studies were performed in 28 patients undergoing primary radiation therapy for invasive cervical cancer. T2-weighted spin-echo pulse sequences with long repetition times (2,500 msec) and echo times (30-100 msec) were used at a field strength of 1.5 T. Eighteen tumors responded promptly to radiation therapy with a volume reduction and significant decrease of signal intensity in the early posttreatment phase (1-3 months) and with total tumor regression at 1-6 months (immediate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 0 publications
2
42
0
2
Order By: Relevance
“…Similarly, Mayr et al [9] reported that for the pre-treatment measurement both the diameter-based method and ROI volumetry in cervical carcinoma treated with radiation therapy alone provided similar predictive accuracy, particularly for patients with small (<40 cm 3 ) and large (≥100 cm 3 ) pre-radiotherapy tumor size. However, the predictive value of tumor volume in our results measured by either method has limitation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Similarly, Mayr et al [9] reported that for the pre-treatment measurement both the diameter-based method and ROI volumetry in cervical carcinoma treated with radiation therapy alone provided similar predictive accuracy, particularly for patients with small (<40 cm 3 ) and large (≥100 cm 3 ) pre-radiotherapy tumor size. However, the predictive value of tumor volume in our results measured by either method has limitation.…”
Section: Discussionmentioning
confidence: 91%
“…Accurate staging in cervical carcinoma is essential in therapeutic decision-making, determining prognosis, and comparing the results of different treatment modalities in these inoperable patients. Recently, primary tumor size has been well established in a large number of studies as an important independent predictor to survival in inoperable cervical cancer [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Therefore, the appropriate method and its accuracy for tumor size measurement to provide p-value comparing <20 mL and 20-39 mL groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 ). A delayed response (6-9 months) has been described for large cervical cancers (Engin 2006 ;Flueckinger et al 1992 ). Parametrial fi brosis displaying low SI on T2WI is most evident in areas of previous tumor invasion (Engin 2006 ).…”
Section: Cervix and Vaginamentioning
confidence: 99%